A novel viscous dissecting gel for endoscopic submucosal dissection: a prospective survival study in a porcine model - Saxena, Payal; Simons, Brian W.; Gabrielson, Kathleen; Haito-Chavez, Yamile; Valeshabad, Ali Kord; Kumbhari, Vivek; Singh, Vikesh K.; Lennon, Anne Marie; Canto, Marcia Irene; Pasricha, Pankaj J; Kalloo, Anthony; Khashab, Mouen A. (Endoscopy, 2014)
Background and study aims: Endoscopic submucosal dissection (ESD) is a technically challenging procedure. A novel gel can facilitate ESD due to its submucosal dissecting properties. This prospective porcine survival study evaluated clinical and histologic parameters of hybrid ESD using the gel.Patients and methods: Gastric submucosal lesions were created in six pigs and hybrid ESD was performed. Healing was assessed weekly until necropsy at Day 28.Results: En bloc resection was achieved in all lesions (mean size 40.7 mm). The mean total procedure time was 13.5 minutes and the mean resection time was 5.5 minutes. The mean total histologic injury score was 4. At necropsy, four ulcers had healed completely and two were < 6 mm in size.Conclusion: Hybrid ESD of large gastric lesions in a porcine model can be facilitated by the novel gel, dramatically reducing procedure and resection times by eliminating the need for time-consuming submucosal dissection. The novel gel is safe and easy to use, and has the potential to simplify ESD. Further prospective human studies are needed to validate these findings.